PERSEPSI MEREK MEWAH UNTUK MEMBANGUN MINAT BELI - Nugraha, Rifki Candra; Hurriyati, Ratih; Utama, Dian Herdiana (Business Education Program of Universitas Pendidikan Indonesia, 2016)
Purpose - This study was conducted to know the effect of luxury brand perception on purchase intention.The design / methodology / approach - this study was conducted over a period of less than one year, the research design used was cross sectional method. This research uses descriptive and verifikatif approach with explanatory survey method. A total of 370 respondents as a sample using simple random sampling. Questionnaire research is used as a research instrument to collect data from respondents and data analysis techniques used are simple linear regression.Findings - the perception of luxury brands have a significant effect on purchase intention.Originality - differences are found in independent variables, research objects and methods, population and sample studies, research periods, measuring instruments and research results, as well as sources of foreign theories and journals and foreign books.